A novel method based on membrane distillation for treating acid mine drainage: Recovery of water and utilization of iron. (September 2021) - Wang, Yuxiang; Wang, Jianbing; Li, Zhongyi; Wang, Huijiao; He, Xuwen; Wang, Chunrong
Abstract: Rapid and highly efficient treatment of acid mine drainage (AMD) is still challenging due to the low pH and high metal concentrations in it. This research focuses on a novel treatment method of AMD using direct contact membrane distillation (DCMD) and photocatalysis to recover water and utilize iron. In the DCMD process without pretreatment, the flux decreased by 93.38%. If pretreated by adding sodium oxalate, scale formation potential was effectively mitigated due to the removal of calcium and complexing of iron. For the treatment of the pretreated AMD (PAMD), 60% of water was recovered in the DCMD process with the flux decrease of 22%. The concentrate obtained from the DCMD process demonstrated high photocatalytic activity in the methylene blue (MB) degradation in an aqueous solution. In addition, the Fe (III)-oxalate complexes in the concentrate were reduced to insoluble Fe (II)-oxalate with visible light irradiation, which could be separated by sedimentation and used as a Fenton catalyst. Hence, this novel method exhibits great advantages on effectively inhibiting DCMD membrane fouling during AMD treatment, producing high-quality distillate with low conductivity, and realizing near zero-discharge of AMD. Graphical abstract: Image 1 Highlights: Inorganic membrane fouling was investigated in DCMD process treating of actual AMD. MD process was improved as the added sodium oxalate can precipitate Ca and complex Fe. Concentrate from MD process treating PAMD was active for the PC degradation of MB. Fe 2+ oxalate separated from the concentrate by irradiation is used as Fenton catalyst. MD with pretreatment and photocatalysis is helpful for near-zero discharge of AMD.